2017
DOI: 10.1053/j.ajkd.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine-Induced Crystalluria Causing Severe Acute Kidney Injury

Abstract: Sulfasalazine is an anti-inflammatory agent commonly used in the treatment of autoimmune conditions such as inflammatory bowel disease and rheumatoid arthritis. Sulfasalazine is converted by gut bacteria into sulfapyridine and the clinically active metabolite 5-aminosalicylic acid (5-ASA), and its efficacy is proportional to the 5-ASA concentration within the intestinal lumen. Renal complications are commonly reported for the chemically similar 5-ASA derivative mesalamine, but are not well-known side effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…However, the efficacies of these drugs are uncertain (Nielsen et al, 2016). In addition, long-term administration of sulfasalazine and Mesalazine could induce many side effects such as chronic hepatitis, liver fibrosis, renal complications, pulmonary toxicity, blood dyscrasias, sexual dysfunction, and even rarely pancreatitis (Durando et al, 2017;Sehgal et al, 2018). Monoclonal antibodies are associated with high risk of losing response after long term use (Moss et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacies of these drugs are uncertain (Nielsen et al, 2016). In addition, long-term administration of sulfasalazine and Mesalazine could induce many side effects such as chronic hepatitis, liver fibrosis, renal complications, pulmonary toxicity, blood dyscrasias, sexual dysfunction, and even rarely pancreatitis (Durando et al, 2017;Sehgal et al, 2018). Monoclonal antibodies are associated with high risk of losing response after long term use (Moss et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed SSZ can inhibit cell proliferation of breast cancers including MCF-7 cells (ER-negative breast cancer) and MDA-MB-231 cells (TNBC) though many signal pathways remain to study 12, 13. However, SSZ can cause adverse effects in human containing mitochondrial dysfunction and acute renal injury 14, 15. In order to promote anti-cancer activity and decrease SSZ-induced adverse effects, many studies suggested SSZ in combination with other therapies may be a useful treatment for cancer treatment 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…29 A previous study showed that sulfasalazine caused oxidative stress and renal injury. 30 Also, some studies have shown mesalazine administration is associated with renal injury. 31,32 Similar to the present findings, mesalazine treatment in vivo showed decreased kidney mitochondrial SDH activity, mitochondrial glutathione (GSH) depletion, mitochondrial depolarization, increase in mitochondrial swelling mitochondrial ROS, and lipid peroxidation in treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…The change in mitochondrial volume, due to the colloidal osmotic effects of solute flux into and out of the mitochondrial matrix, was measured by monitoring the absorbance at 540 nm (A 540 ). 23 Briefly, after incubation of mitochondria isolated from rat heart with mesalazine (0, 25, 50, and 100 mM) at 30 C for 5 minutes in swelling buffer (70 mM sucrose, 230 mM mannitol, 3 mM HEPES, 2 mM Tris-phosphate, 5 mM succinate, and 1 mM of rotenone), absorbance was measured at 540 nm at 60 minutes (5,30, and 60 minutes) with an ELISA reader (Tecan, Rainbow Thermo). A decrease in the absorbance indicates an increase in mitochondrial swelling.…”
Section: Determination Of Mitochondrial Swellingmentioning
confidence: 99%